MITIGASI MASYARAKAT PASCA BENCANA BANJIR MUSIMAN DI DESA WONOASRI KABUPATEN JEMBER - Mulyaningrum, Rr Dewi Ikawati; Mulyono, Joko (Jurnal ENTITAS SOSIOLOGI, 2019)
As elaborated in a research background, the flood has occurred in Wonoasri Village since 1954, and the disaster frequently occurs every year. A seasonal flood happens every year, which causes physical and non-physical damages. The flood damages agricultural lands, animal farms and wipes away inhabitants’ residence, facilities, and infrastructure, resulting in serious impacts on the inhabitants’ economy. In such condition, the people that live in the Village of Wonoasri feel worried and scared. In this case, the people have mitigation skill that can be performed after a seasonal flood, and they carry out the mitigating activities in the process of flood recovery, such mitigating aspects by the people, particularly related to the social aspect, allude to Ecological recovery through non-physical and physical means. Ecological recovery by non-physical means represents an effort to deal with social functions. The research focused on the description approach with case study type, using purposive sampling. The theory employed alluded to Constructivist theory by Petter L Begger, which especially pertains to elaborating the process of knowledge in daily life as derived from human thinking and acting, and those maintained in reality. The process of knowledge itself consisted of the social reality that was derived from the process of knowledge. In emphasizing awareness, human’s awareness is always focused on an object. The fundamental of awareness could not be made obvious because humans only have awareness of the phenomenon. Keywords: Construction, Seasonal flood, Mitigation, Human Ecology